INTERPRETATION OF POLYSEMIC WORDS IN ENGLISH-UZBEK BILINGUAL DICTIONARIES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In bilingual dictionaries, an important role in the disclosure of lexical and semantic features, semantic subtleties, and semantic possibilities of the studied language unit is played by a dictionary micro-device – a dictionary entry.